COMIC BOOK RENTAL APPLICATION ELEX MEDIA KOMPUTINDO WITH VISUAL BASIC 6.0 PROGRAMMING - Rizky Harrie Mandey; Aqwam Rosadi K. Skom, MM Aqwam Rosadi K. Skom, MM (Jurnal Sistem Informasi, 2003)
To improve the efficiency of the comic book and a list of income renters and rentaltransaction processing in a computerized comic book writer inspired to create a comicbook rental applications using Visual Basic 6.0 programming, making it easier andspeed up data processing, printing reports, information on tenant list after the expirydate tempo, and comic book rental transaction counts.Authors aim to make this application, so that people familiar with the use ofcomputers in everyday life, especially for owners of rental book stores or kiosks, andstaff working at the store or kiosk.